2021
DOI: 10.1016/j.eclinm.2021.101139
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient and inpatient anticoagulation therapy and the risk for hospital admission and death among COVID-19 patients

Abstract: Background: Coronavirus disease 2019 (COVID-19) is associated with a hypercoagulable state. Limited data exist informing the relationship between anticoagulation therapy and risk for COVID-19 related hospitalization and mortality. Methods: We evaluated all patients over the age of 18 diagnosed with COVID-19 in a prospective cohort study from March 4th to August 27th, 2020 among 12 hospitals and 60 clinics of M Health Fairview system (USA). We investigated the relationship between (1) 90-day anticoagulation the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 55 publications
1
33
0
4
Order By: Relevance
“… 63 The results of another prospective cohort study conducted on 6195 patients in 14 hospitals and 60 clinics in the United States show that SARS-CoV-2 is associated with a state of hypercoagulability and that the presence of cardiovascular, immunological and coagulatory comorbidities has been associated with a higher risk of death, especially for inpatients, ICUs and mechanically ventilated and non-ventilated patients. 64–66 …”
Section: Discussionmentioning
confidence: 99%
“… 63 The results of another prospective cohort study conducted on 6195 patients in 14 hospitals and 60 clinics in the United States show that SARS-CoV-2 is associated with a state of hypercoagulability and that the presence of cardiovascular, immunological and coagulatory comorbidities has been associated with a higher risk of death, especially for inpatients, ICUs and mechanically ventilated and non-ventilated patients. 64–66 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to a growing body of evidence that has failed to show benefits of intermediate‐dose thromboprophylaxis among adults hospitalized with COVID‐19. 7 , 11 , 22 , 23 , 24 , 25 , 26 , 27 A small clinical trial showed no difference in risk of thrombosis, ECMO, or death between standard and intermediate doses with weight‐based adjustments. 22 In our subgroup analyses, where we applied weight‐based adjustments, we again found increases in risk of therapeutic anticoagulation as a proxy for thrombosis, severe disease, and death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since the outbreak of COVID-19, LMWH has been widely used for anticoagulation in older COVID-19 patients (Kreidieh and Temraz, 2021). In patients with proximal DVT and PE, LMWHs are preferred over oral anticoagulants and UFH (Hozayen et al, 2021). In-hospital COVID-19 patients who were on anticoagulation with LMWHs or UFH had a significantly reduced risk of mortality (hazard ratio 2.26, 95% CI 1.17-4.37).…”
Section: Discussionmentioning
confidence: 99%